Mind the Seat Limit: On Capacity Management in Public Automated Shuttles - Mirnig, Alexander G.; Gärtner, Magdalena; Wallner, Vivien; Füssl, Elisabeth; Ausserer, Karin; Rieß, Jannik; Meschtscherjakov, Alexander (Frontiers in Human Dynamics, 2021)
With ever growing automation of public transport automated shuttles offer an attractive alternative in areas where traffic regulations limit the deployment of large buses (city centres) or where low degrees of utilization renders the manual vehicles operation non-economical (last mile). The low capacities of shuttles in combination with the human factor (driver or conductor) makes capacity management a greater challenge for the user. Capacity management describes the allocation of available seats in a vehicle, e.g., when buying a ticket. In this paper, we present the results of series of studies where capacity management in automated shuttles has been tested via instruments that are currently available in public transit (audio announcements, in-shuttle displays, booking apps). We found that measures during and after boarding are not sufficient and that capacity management in automated shuttle requires a more detailed planning of pre-boarding stages; when boarding automated shuttles as opposed to non-automated public buses the flexibility is reduced. The paper concludes with discussion and recommendations for an optimal capacity management d.